2012
DOI: 10.1177/2150131912464887
|View full text |Cite
|
Sign up to set email alerts
|

Patients Whose Physicians Recommend Colonoscopy and Those Who Follow Through

Abstract: Socioeconomic factors are associated with receipt of a colonoscopy recommendation. Fewer than one third of patients had documentation of a physician colonoscopy recommendation and of those, less than half followed through.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Fifty-six percent of the sample in this study went on to be screened for CRC following a physician recommendation for screening, with no significant differences between visits with and without observer-coded use of physician persuasion. This number compares favorably to a recent study examining post-physician recommendation rate of colonoscopy in a Midwestern practice-based research network, which found that only 39 % of participants followed through with a colonoscopy after a physician recommendation [46]. Similarly, another study conducted in two academic primary care clinics in California found that, following a discussion about CRC screening with their physicians, only 45 % of patients completed the recommended screening [11].…”
Section: Discussionsupporting
confidence: 51%
“…Fifty-six percent of the sample in this study went on to be screened for CRC following a physician recommendation for screening, with no significant differences between visits with and without observer-coded use of physician persuasion. This number compares favorably to a recent study examining post-physician recommendation rate of colonoscopy in a Midwestern practice-based research network, which found that only 39 % of participants followed through with a colonoscopy after a physician recommendation [46]. Similarly, another study conducted in two academic primary care clinics in California found that, following a discussion about CRC screening with their physicians, only 45 % of patients completed the recommended screening [11].…”
Section: Discussionsupporting
confidence: 51%
“…The influence of income on congruent self-reporting, consistent across both multinomial and binomial analyses, may be due to several interrelated factors. Previous data indicate that higher income patients are more likely to be prescribed CRC screening, 44,45 and evidence indicates that having received a doctor’s recommendation for screening increased the probability of accurately recalling past screenings. 12 When considered together, these data suggest mediational paths in which higher income increases the probability of doctor’s recommendation for CRC screening, which decreases the odds of incongruently self-reporting positive screening.…”
Section: Discussionmentioning
confidence: 99%
“…This finding merits further investigation. The second sociodemographic factor associated with colonoscopy completion, higher income, has been found to be predictive for colonoscopy completion [9, 45-48] with only rare exception [49]. …”
Section: Discussionmentioning
confidence: 99%